Back cover: Reductive Metabolism of Xanthohumol and 8‐Prenylnaringenin by the Intestinal Bacterium Eubacterium ramulus. Issue 2 (21st January 2019) - Paraiso, Ines L.; Plagmann, Layhna S.; Yang, Liping; Zielke, Ryszard; Gombart, Adrian F.; Maier, Claudia S.; Sikora, Aleksandra E.; Blakemore, Paul R.; Stevens, Jan F.
Abstract : Mol. Nutr. Food Res. 2019, 63, 1800923 DOI: 10.1002/mnfr.201800923 Gut microbial metabolism of xanthohumol produces estrogenic metabolites, notably 8‐prenylnaringenin. In article number 1800923, Jan F. Stevens and co‐workers show that 8‐prenylnaringenin is not the end product of metabolism by gut microbes, shedding new light on the perceived pro‐estrogenicity of xanthohumol.